Non pilot and pilot aided least square channel estimation algorithm in MIMO-OFDM system / Nursarah Ainaa Abdul Halim - Abdul Halim, Nursarah Ainaa (2013)
Wireless communication is a developed technology and had been widely used nowadays, so the developments in digital communication are rapidly increasing to meet the ever increasing demand of higher data rates. In order to meet the high data rate, low complexity requirements of the future mobile communication systems, Multiple input Multiple output (MIMO) is introduced and integrated with Orthogonal Frequency division Multiplexing (OFDM) scheme to reduce Inter-Symbol Interference (ISI). With such integration, channel complexity is increased. Therefore several channel estimation techniques have been proposed to improve the estimation process and reduce the computational complexity by exploiting certain characteristics of the channel model. This project is about analyze and implement channel estimation techniques for MIMO-OFDM Systems with Least Squares (LS) Algorithm channel estimation by comparing non pilot and pilot aided result and the result is supposed the Pilot aided will have a better performance.